Limiares de dor à pressão, amplitude de movimento e força cervicais em sujeitos com dor no ombro: estudo transversal de casos e controles - Rebelatto, Marcelo Nascimento (2020)
Shoulder pain is one of the main musculoskeletal disorders; however, there are difficulties in its assessment and diagnosis. Considering regional interdependence, a patient's primary symptom may be related to impairments in various regions and systems of the body regardless of proximity to the primary symptom. The relationship between the shoulder and the cervicothoracic spine has less previous evidence, which would improve the description and decision-making in these individuals. In this sense, the objectives of this thesis were: 1) to determine the intra and inter-rater reliability to assess the strength of the cervical muscles in individuals with shoulder pain. 2) identify if there are differences between the assessments of sensitivity, range of motion (ROM) and cervical strength of subjects with and without shoulder pain. For the first study, cervical muscle strength was assessed in 31 individuals with shoulder pain using a portable dynamometer and reliability was analyzed using the Intraclass Correlation Coefficient (CCI), standard error of measurement (SEM) and Minimum Detectable Change (MDC). It was concluded that the portable hand held dynamometer has excellent intra-rater reliability and good to excellent inter-rater reliability for manual cervical dynamometry. In the second study, 48 individuals with shoulder pain and 48 asymptomatic of both genders, aged between 18 and 60 years, who did not have cervical dysfunction were assessed. Sensitivity (pressure pain threshold), ROM (goniometry with cervical range of motion) and cervical strength (manual dynamometry) assessments were performed in all individuals. It was concluded that individuals with shoulder pain have greater cervical sensitivity and less cervical mobility than asymptomatic individuals. In addition, older age, pain and dysfunction tend to be associated with poorer performance in cervical assessments.